2022
DOI: 10.1038/s41467-022-34346-x
|View full text |Cite|
|
Sign up to set email alerts
|

Promoting anti-tumor immunity by targeting TMUB1 to modulate PD-L1 polyubiquitination and glycosylation

Abstract: Immune checkpoint blockade therapies targeting the PD-L1/PD-1 axis have demonstrated clear clinical benefits. Improved understanding of the underlying regulatory mechanisms might contribute new insights into immunotherapy. Here, we identify transmembrane and ubiquitin-like domain-containing protein 1 (TMUB1) as a modulator of PD-L1 post-translational modifications in tumor cells. Mechanistically, TMUB1 competes with HECT, UBA and WWE domain-containing protein 1 (HUWE1), a E3 ubiquitin ligase, to interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…39 Recent studies indicate that TMUB1 greatly facilitates antitumor immunity and inhibits tumor growth in mice, and it can serve as a potential candidate target to improve the prognosis of cancer-immune patients. 40 Our study demonstrated that TMUB1 knockdown blocked embryo loss and inhibited LPSinduced inflammation and apoptosis. These findings indicate abnormal expression of TMUB1 is tightly linked to a series of illnesses and highlight the potential significance of TMUB1 as a biological marker.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…39 Recent studies indicate that TMUB1 greatly facilitates antitumor immunity and inhibits tumor growth in mice, and it can serve as a potential candidate target to improve the prognosis of cancer-immune patients. 40 Our study demonstrated that TMUB1 knockdown blocked embryo loss and inhibited LPSinduced inflammation and apoptosis. These findings indicate abnormal expression of TMUB1 is tightly linked to a series of illnesses and highlight the potential significance of TMUB1 as a biological marker.…”
Section: Discussionmentioning
confidence: 54%
“…TMUB1 is demonstrated to inhibit the proliferation of rat liver cells and negatively modulate liver regeneration 39 . Recent studies indicate that TMUB1 greatly facilitates antitumor immunity and inhibits tumor growth in mice, and it can serve as a potential candidate target to improve the prognosis of cancer‐immune patients 40 . Our study demonstrated that TMUB1 knockdown blocked embryo loss and inhibited LPS‐induced inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…It has been revealed that PD-L1 is predominantly degraded through two distinct pathways: proteasome and lysosome. Several studies have explored the regulation of PD-L1 proteasomal degradation, with some insights indicating that inhibiting PD-L1 glycosylation or deubiquitination promotes PD-L1 degradation via proteasomes 30 , 34 , 35 . Other research has suggested that HIP1R targets PD-L1 to lysosomal degradation and alters T cell-mediated cytotoxicity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been a plethora of treatments based on targeting various proteins in cells to trigger anti-tumor immunity over the years. 69, 70 Here, we discovered an unprecedented mechanism in which depleting hnRNPM can elevate antiviral signaling in tumors via cryptic exon-derived long stem-like dsRNAs, triggering a type I interferon response. Such immunity-enhancing properties of hnRNPM-regulated cryptic exons possess vast clinical potential and may expand horizons of treatment for diseases other than cancer.…”
Section: Discussionmentioning
confidence: 99%